The P2TP2A’s Effort to Cope with the Intensification of Sexual Abuse of Children in Perspective of the Islamic Family Law (A Case Study at the City of Banda Aceh) - Juanda, Satria; Gani, Burhanuddin Abdul; Rahmatillah, Syarifah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Law Number 35 of 2014 Article 1 Paragraph (2) Regarding Child Protection includes all activities designed to guarantee and protect children and their rights so that they can live, grow, and develop in accordance with human dignity, and receive protection from violence and discrimination. However, sexual violence against minors continues to be a reality in our society. According to data from P2TP2A Banda Aceh, there were 13 cases in 2018 and 19 cases in 2019. The author wishes to know how effective P2TP2A Banda Aceh’s efforts are in combating sexual violence against minors and what obstacles this particular institution faces in this regard. This is a qualitative case study research investigating strategies used to cope with abuses against minors. The results indicate providing guidance and education are two important strategies used in its effort to cope it sexual abuses against minors. In addition, legal assistance services, health and psychological services, safe housing services (shelter), social rehab services are also provided for this cause. The obstacles that P2TP2A Banda Aceh faces in combating sexual violence against children are familial disgrace, trauma victims, infrastructure, and facilities. In addition to P2TP2A Banda Aceh, the Banda Aceh Police and LBH (Legal Aid Institute) of Banda Aceh participated in combating the rising incidence of sexual violence against minors in the city of Banda Aceh. This study also suggests that the Banda Aceh Police conducted investigations after receiving complaints from the public. And research conducted by LBH Banda Aceh indicates that the efforts made include providing legal assistance to victims.